Key recommendations in promoting biobanking and precision medicine: dissemination strategies of the BRoTHER-Biobank Network - Winter, Lina; Seidler, Deborah; Snítilá, Monika; Karlíková, Marie; Topolčan, Ondrej; Burkhardt, Ralph; Niedermair, Tanja; Brochhausen, Christoph (Biopreservation and biobanking, 2025)
Biobanking is essential for advancing precision medicine. However, challenges persist in raising public awareness and addressing data protection concerns. This brief report outlines dissemination strategies by the Central Biobank Regensburg (Zentrale Biobank Regensburg—ZBR) and the BRoTHER (Biobank Research on Telemedical Approaches for Human Biobanks in a European Region) network to engage relevant target groups. In this context, five key recommendations are derived: (1) tailoring communication to audience needs, (2) using diverse outreach methods, (3) enhancing digital presence, (4) fostering cross-border collaboration, and (5) securing dedicated funding. These strategies aim to promote the social and scientific benefits of biobanking while ensuring its sustainability.
Gesehen am 01.07.2025